1990
DOI: 10.1080/15287399009531370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selected chemicals on the glutathione status in the male reproductive system of rats

Abstract: Previous studies have suggested a significant role for reproductive tract glutathione in protecting against chemical-induced germ-cell mutations. Therefore, a number of compounds were tested for their ability to perturb glutathione levels in the testes and epididymides as well as liver following single acute dosages to rats. Phorone (250 mg/kg), isophorone (500 mg/kg), and diethyl maleate (500 mg/kg) significantly reduced glutathione in the liver and in both reproductive organs examined. Methyl iodide (100 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 24 publications
0
3
0
3
Order By: Relevance
“…Other researchers have shown that conjugation of AFB 1 -epoxide with glutathione by GST protects against genetic damage. In rats, chemically induced depression of testicular glutathione caused a significant increase in dominant lethal mutations by ethyl methanesulfonate [Teaf et al, 1987] and enhanced binding of this mutagen to sperm heads [Gandy et al, 1990]. Also, GST is thought to play a major role against testicular toxicity by ethylene oxide in the rat [Mori et al, 1989].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other researchers have shown that conjugation of AFB 1 -epoxide with glutathione by GST protects against genetic damage. In rats, chemically induced depression of testicular glutathione caused a significant increase in dominant lethal mutations by ethyl methanesulfonate [Teaf et al, 1987] and enhanced binding of this mutagen to sperm heads [Gandy et al, 1990]. Also, GST is thought to play a major role against testicular toxicity by ethylene oxide in the rat [Mori et al, 1989].…”
Section: Discussionmentioning
confidence: 98%
“…Several authors have shown that glutathione and GST play an important role in protecting the testis against DNA damage by various genotoxic agents [Teaf et al, 1987;Mori et al, 1989;Gandy et al, 1990]. This mechanism may also play an important role in protecting the testis against DNA damage by AFB 1 .…”
Section: Introductionmentioning
confidence: 97%
“…Darüber hinaus treten wahrscheinlich Konjugate mit Glutathion auf: Isophoron (500 mg/kg KG, einmalig, i.p.) führte bei Sprague-Dawley-Ratten zu signifikanter Abnahme des Glutathiongehaltes in Leber (40%; maximale Reduktion 4 Stunden nach Applikation), Hoden (82%; maximale Reduktion 4 Stunden nach Applikation) und Nebenhoden (72%; maximale Reduktion 8 Stunden nach Applikation) (Gandy 1988;Gandy et al 1990). Um zu klären, ob Isophoron oder seine Metaboliten mit E2V-Globulin assoziiert sind, wurden männliche Ratten (k. w.…”
Section: Abb 1 Metabolismus Von Isophoronunclassified
“…2 Stunden, 1 und 15 Tage nach Behandlung war die 3 H-Ethylmethansulfonat-Bindung gegenüber den Kontrollen unverändert. Ethylmethansulfonat induziert DominantLetal-Mutationen, wobei ein Zusammenhang mit der GSH-Depletion diskutiert wird (Gandy 1988;Gandy et al 1990). Durch die Glutathiondepletion kann es möglicherweise zu einer erhöhten Bindungsrate alkylierender Substanzen kommen.…”
Section: Wirkung Auf Haut Und Schleimhäuteunclassified
“…Gabe von 500 mg Naphthalin/kg KG an männliche Sprague-Dawley-Ratten wurde eine mehrstündige Abnahme des Glutathiongehalts in Leber � Nebenhoden � Hoden gefunden (Gandy et al 1990). Eine Naphthalinexposition über das Trinkwasser führte bei Mäusen, Ratten und Meerschweinchen zu einer verminderten Spermatogenese und einer verzögerten Entwicklung der Nachkommen (k.w.A.…”
Section: Fertilitätunclassified